2022
DOI: 10.1007/s13346-022-01121-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of wound healing properties of hydro-diab hydrogel loaded with green-synthetized AGNPS: in vitro and in ex vivo studies

Abstract: In diabetic patients, the presence of neuropathy, peripheral vascular diseases and ischemia, leads to the formation of foot ulcerations with a higher risk of infection because the normal response to bacterial infection is missing. In the aim to control and treat diabetic foot ulcerations (DFUs), wound dressings that are able to absorb exudate, to prevent infections, and to promote wound healing are needed. For this reason, the aim of the present research was to synthetize a biocompatible hydrogel (called HyDrO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The cell viability was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell viability was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The major bioactives contained in olive leaves are oleuropein, hydroxytyrosol, chlorogenic acid, caffeic acid, verbascoside and rutin. Among them, oleuropein is the main polyphenol contained in olive leaf extracts and it is widely used to treat skin diseases and wounds, showing the ability to accelerate the healing process [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Washes with FACS buffer were performed and additional FACS buffer with propidium iodide (PI) was added. Expression of CD54, CD86 and cell viability levels were then assessed in the cytofluorometer, and the results were calculated as previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, traditional industrially synthesized AgNPs are costly, complicated to generate and cytotoxic, so an increasing number of scientists are turning their attention to biosynthetic AgNPs. Ruffo et al loaded green synthetic AgNPs into CMC hydrogels and confirmed that they possess good antioxidant, anti-inflammatory and antimicrobial activities for the treatment of DUs [ 244 ]. Krishnan et al showed that biologically derived AgNPs reduced the mRNA and protein expression of MMP-2 and MMP-9 in wound granulation tissue and promoted early wound healing in diabetic mice [ 243 ].…”
Section: Bioactivators For Dusmentioning
confidence: 99%